Multiple nonvolatile skyrmion states in nanostructured synthetic antiferromagnetic multilayers - Ma, Mangyuan (2023)
Magnetic skyrmions have promising applications as nonvolatile memory for their particlelike and topological-protected features. The recently reported artificial skyrmion has shown a better prospect due to its controllable size and site. Here, we propose and experimentally demonstrate multiple nonvolatile skyrmion states in nanostructured synthetic antiferromagnetic [Pt/Co]4/Ru/[Co/Pt]4 multilayers at room temperature. Our magneto-optical Kerr effect measurements of major and minor reversal curves reveal that the skyrmion can exist at zero field with memristive behavior. Using the observed multiple skyrmion states, nonvolatile memory behavior is demonstrated. Our results provide evidence for the concept of skyrmion-based nonvolatile memory, i.e., skyrmion-based memristors and artificial synapses or neurons.